(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: this article provides a comparative analysis of the classification of affixes in the English and Uzbek languages. Affixes are an integral part of word formation in both languages, playing a crucial role in deriving new words and modifying the meaning and function of existing ones. The study examines the different types of affixes, including prefixes, suffixes, and infixes, and how they are categorized and utilized in each language.